The Development Of Vehicle Management System Textbook Based On Simulation Softwares - Wachid Yahya; Dwi Iskandar (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
This study was designed to develop textbook of vehicle management system based on simulation softwares. The research method used Research and Development (R&D) with a model developed by Dick and Carry, an ADDIE development model that contains five tools; device analysis, design, development, implementation, and evaluation. Analysis of the data used descriptive method. Ther research subjects were the second semester students of the D3 Automotive Engineering Study Program of the Indonusa Polytechnic of Surakarta academic year 2018/2019. The results of this study were the creation of textbooks Vehicle Management Systems integrated with simulation softwares, which were Proteus version 7.07 and Fluidsim version 3.6. The textbook was assessed by 3 learning device experts, 3 lecturers and has been tested on students. The assessments show the percentage of achievements of 92.94% of the material experts, 86.03% of the learning device experts, 85.07% of the lecturers, and 86.62% of the students. This textbook has advantages from aspects of learning that are in accordance with learning 4.0, namely by combining theory and simulation that can be accessed via smart phones or computers connected to the internet.